2001
DOI: 10.1557/jmr.2001.0064
|View full text |Cite
|
Sign up to set email alerts
|

Improved tensile creep properties of yttrium- and lanthanum-doped alumina: a solid solution effect

Abstract: The tensile creep behavior of yttrium-and lanthanum-doped alumina (at dopant levels below the solubility limit) was examined. Both compositions (100 ppm yttrium, 100 ppm lanthanum) exhibited a uniform microstructure consisting of fine, equiaxed grains. The creep resistance of both doped aluminas was enhanced, compared with undoped alumina, by about two orders of magnitude, which was almost the same degree of improvement as for materials with higher dopant levels (in excess of the solubility limit). In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Experimental studies however indicate that below the solubility limit and at the same dopant concentration and sintering conditions, La and Y doped samples have approximately the same grain size. 43,46,47 The effect on creep resistance is also reported to be either very similar 45,46 or even less for La than for Y. 47 From the present results two possible indications as to why La is not more effective than Y can be gained.…”
Section: Lanthanum Segregationsupporting
confidence: 56%
See 2 more Smart Citations
“…Experimental studies however indicate that below the solubility limit and at the same dopant concentration and sintering conditions, La and Y doped samples have approximately the same grain size. 43,46,47 The effect on creep resistance is also reported to be either very similar 45,46 or even less for La than for Y. 47 From the present results two possible indications as to why La is not more effective than Y can be gained.…”
Section: Lanthanum Segregationsupporting
confidence: 56%
“…Both dopants are known to decrease grain growth during sintering 42,43 and increase the high-temperature creep resistance [44][45][46][47][48][49] of ␣-alumina. Grain boundary segregation rather than second phase precipitation is the cause of these effects, as they occur below the solubility limit.…”
Section: Lanthanum Segregationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanthanide (Ln 3+ ) ion-doped Al 2 O 3 is particularly appealing, since the local environment of the doped ions is known to critically influence the optical and mechanical properties of Al 2 O 3 due to the large size mismatch between Ln dopants and aluminum678. For example, the presence of dopants (ytterbium, gadolinium or lanthanum) strengthens the grain boundaries of alumina, largely affecting the mechanical properties91011. A study conducted on doping alumina with lanthanum (La) showed a reduction in the phase transformation (γ → α) temperature by 100 °C, thus increasing the thermal stability of γ-Al 2 O 3 12.…”
mentioning
confidence: 99%
“…It should be noted that impurities often segregate to grain boundaries or other defects and may thereby affect thermomechanical and kinetic properties. [28][29][30] In this study, we wish to identify which (possibly non-linear) combination(s) of processing variables is (are) most correlated with microstructural abnormality. To accomplish this aim, after the spark-plasma sintering of specialty alumina powders, we compiled statistics for microstructures associated with grain growth at some annealing temperature.…”
Section: Applicationsmentioning
confidence: 99%